IMPACT OF READING INTEREST AND LIBRARY FACILITY UTILIZATION ON SOCIAL SCIENCE LEARNING ACHIEVEMENT OF 6TH GRADE STUDENTS - Nurhidayat, Afandi; Nisa, Ana Fitrotun (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
In today’s learning, students tend to prefer listening activities over reading. Therefore, the world of education has an important role in addressing this phenomenon by providing appropriate supporting facilities, one of which is a school library representative of students’ learning needs. Social studies subjects emphasize reading and comprehension competencies. If this aspect is not a primary concern in improvement efforts, it is feared that students’ reading interests will continue to decline. This concern can also impact student learning outcomes, especially in social studies subjects. This research aims to (1) analyze the extent to which reading interest influences student learning outcomes in social studies subjects in 6th grade at SD Negeri Jagamangsan 1, (2) examine the impact of library facility utilization on student learning outcomes, and (3) investigate the simultaneous influence between reading interest and library utilization on student learning outcomes. The research method used is a quantitative approach with a correlational research type. The research sample consisted of 45 students from SD Negeri Jagamangsan 1, selected using a total sampling technique. Data collection techniques were carried out through questionnaires and documentation. The research results indicate that a significance value of 0.001<0.005 and an F-count value of 8.302>3.21 were obtained based on the F-test. Thus, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. It proves that there is a significant relationship between the reading interest variable (X1) and the utilization of library facilities (X2) on student learning outcomes (Y).